Epidemiology and Risk Factors for Nosocomial Infections in Left Ventricular Assist Device Recipients - Simone Mornese Pinna; Silvia Corcione; Elena Cavallone; Nour Shbaklo; Davide Vita; Ilaria De Benedetto; Giorgia Montrucchio; Daniela Pasero; Anna Chiara Trompeo; Andrea Costamagna; Luca Brazzi; Mauro Rinaldi; et al. (Life, 2024)
Left ventricular assist devices (LVADs) have been increasingly used as a valid option to improve the prognosis and reduce the symptoms of end-stage heart failure. However, long-term complications, mostly infections and coagulation disorders, are frequent. We described the epidemiology and risk factors for nosocomial infections (NIs) in a cohort of adult patients who underwent continuous-flow LVAD implant between January 2010 and December 2017 in Turin, Italy. Secondary outcomes were the prevalence of multidrug-resistant (MDR) bacteria and mortality. Results: Overall, 64 LVADs were implanted. A total of 32 (50%) patients experienced at least one episode of NI, with a total of 46 infectious events. VAD-related infections occurred in 22 patients (68.8%). Non VAD-related NIs occurred in 12 patients (37.5%), mainly low respiratory tract infections. Length of intensive care unit admission was a risk factor for NI (OR 1.224, 95%CI; 1.049, 1.429). Gram-negative bacilli were responsible for 58.8% of VAD-related infections and 79.5% of non-VAD related infections. In sixteen patients (50%), at least one episode of infection was related to an MDR strain. INTERMACS class and length of MV were independent risk factors for NIs by MDR strains (respectively, OR 2.12, 95%CI: 1.08, 6.80; p = 0.02 and OR 1.46, 95%CI: 1.07, 5.52, p = 0.047). In-hospital mortality was 6.3%. No differences in mortality were observed between infected and non-infected patients (p = 0.61) even when caused by MDR strains (p = 0.143). Conclusion: the rate of nosocomial infections in LVAD patients is associated with the length of ICU admission, and the etiology of nosocomial infection after LVAD implant is mainly due to GNB, including a high rate of MDR strains, especially KPC-KP and MDR PA.